Alright I decided I'd create a new topic just because the other one was getting fairly lengthy. I'm having trouble with the following "Higher Derivative" question It states, find y'' by implicit differentiation. x^4 + y^4 = a^4 d/dx (x^4+y^4) = d/dx (a^4) 4x^3 + 4y^3 dy/dx = 4a^3 However, what is the next step from here, I thought perhaps cancelling out all the 4's and leaving it as: x^3 + y^3 dy/dx = a^3 and bring the x^3 over so it's: a^3-x^3 = y^3 dy/dx dy/dx = a^3-x^3 / y^3 However, I'm not positive on that because I was told from a friend that 4a^3 is a constant so it can be equal to 0, thus the dy/dx would be -x^3/y^3. Am I on the right track here or is there an easier way of solving this equation. Thanks a lot guys.